The Influence of Transformational Leadership Style, Work Discipline and Work Motivation on Employee Performance at PT. Putra File Indah - Tri Wahju Wirjawan; Charmila Simanjuntak (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze and examine the effect of transformational leadership style, work discipline, and work motivation on the performance of employees of PT. PUTRA FILE INDAH Son. The method of determining the sample using saturated sampling, so that all the population is used as a sample of 90. Data collection using a questionnaire. The data test technique uses Data Feasibility Test, Classical Assumption Test, influence test, hypothesis test, and coefficient of determination test which will be analyzed using SPSS version 23.0 program. The results showed that transformational leadership style had a positive and significant effect on employee performance by 45.5%, work discipline had a significant effect on employee performance by 56.4%, and work motivation had a positive and significant effect on employee performance by 109.5%